RASIO KONDISI FISIK APLIKASI DAN PERATURAN KESEHATAN DAN KESELAMATAN KERJA (K3) PADA DEPARTEMEN PRODUKSI (STUDI KASUS DI CV. MEGA BOKSINDO SEMARANG-JAWA TENGAH) - Asmoro, Eddi Indro (Students Journal of Engineering, 2015)
Field conditions on the production floor in CV Mega Boksindo prevalent conditions are less favorable, as the temperature of the hot room production floor, equipment and facilities K3 unused andkuntitasnya less balanced, speaking should use extra energy, duplication, and workload over load and many more. This study was limited to review and provide input on the manajamen to see the conditions of theproduction floor of glasses K3. This study compares only real condition with statutory laws and regulations of the K3. Conclusion bias is described as follows K3 functions in the company still not been realized by theproduction operators, utility equipment and facilities K3 for the prevention of illness and accidents, and the impact of the malfunctioning of K3 will cause micro and macro issues for both employees andÂ  companies.KeyWords: Application Ratio K3, K3 Law, Management